Determination of Agricultural Exports in North Sumatra - Muslim, Muhammad; Ridwan, Muhammad; Batubara, Maryam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Export is the process of transporting goods from one country to another legally and export is very important in forming a country’s balance of payments. The purpose of this study was to determine whether gross domestic product, exchange rate, and inflation affect agricultural exports in North Sumatra. This study uses a quantitative approach. Quantitative research is research that emphasizes the analysis of numerical data (numbers) that are processed using statistical methods. The method used in this research is descriptive and verification method. From the research results it is known that the probability of the firm value variable is 0.002816 <0.05, and the F-Statistics value is 6.800019 > 2.64. Based on the results of the simultaneous test it can be seen that the Regional Gross Domestic Product (X1), Exchange Rate (X2), and Inflation (X3) have a positive and significant effect on Regional Exports of North Sumatra together. The R2 value is 0.2619 or 26.19%. This shows that the variables of Regional Gross Domestic Product, Exchange Rate and Inflation can only explain the regional export variable of only 24.90%. While the remaining 75.10% is explained by other variables outside the regression model in this study.